Initial Analysis of the Rainy Season for the Determination of Rice Planting Time in Jembrana Regency - Lestari, Septina Widya; Simpen, I Nengah; Setiyoko, Agit (BULETIN FISIKA; Vol 24 No 2 (2023): BULETIN FISIKA August Edition, 2021)
Jembrana Regency located in Bali Province is one of the districts that have land good enough to be managed. However, some of the area still has the potential to be developed into agricultural land. Analysis of water availability, especially for rice plants, needs to be carried out to determine the time of planting rice, and aims to increase land productivity. The calculation method used is land water balance and plant water balance. The results of the calculation in the form of the percentage of water available for rice plants are used as a reference to determine the planting period in the form of rice planting patterns. From the results of the study, it was found that the decrease in the value of groundwater availability (GA) occurred due to a decrease in rainfall from June to August of around 9 bases to be below Field Capacity (FC). The GA value increases when the rainy season starts from January to April for period I and from September to December for Period II. Rice planting time in Jembrana Regency generally has 2 plantings because it is influenced by availability of groundwater and Rainfall.